The Issue Of Integrated Visual Arts Education At School - Ghalayants, Marina (Զանգակ հրատ.)
This article presents the issues related to the reforms of public education, strengthening of interdisciplinary links of teaching, applied techniques and problems. It concerns the issue of integrated visual Art within the school education system and emphasizes its importance for development of new coming generation within the digital reality of today’s life. The implementation of changes in regular or professional schools first of all means improving the quality of education, developing new levels of knowledge and worldview of students. And in order for students to understand the basics of natural and social sciences, the laws concerning the development of society, first of all it is extremally necessary to change the nature of education, which should not be reproductive, but developing or teaching. With this pedagogical approach, students will be able to solve cognitive problems, make analysis, generalizations, comparisons, reflections, explain a given phenomenon or reality using the knowledge obtained from different subjects. Desk review is used as a research method to select the articles and publications reflecting visual art in education and its integration in school life. Detailed analyses of existing literature prove that integrated visual art in public school enables students’ high- level thinking and productive participation in lessons.
Keywords: Pedagogy